Wild tribes of India - Rowney, Horatio Bickerstaffe (Delhi, 1990)
Without attaching much importance to the distinc tions Aryan and Non-Aryan, it must be conceded that the population of India may be broadly arranged under two distinct divisions-namely, the Aboriginal and the Immigrant. Between Kurrachee on one side and Chittagong on the other there are more than a hundred passes through the mountain barriers that invest the country-that is, the Suleiman, the Hima laya, and the Arracan mountains; and these have given various races of invaders admittance into a land famous for its wealth from time anterior to the dawn of legend and chronicle. On the other hand, the sacred books of the country, which are undeniably ancient, are full of the accounts of an indigenous population that existed in it prior to the races of the Sun and the Moon, and describe minutely the fierce conflicts they waged with the invaders of their hearths and home; and these accounts have evidently a large substratum of truth in them. The aboriginal tribes, we read, were for the most part vanquished and reduced to serfdom, and formed the servile and im purer castes of the Hindu community, amalgamating either wholly or partially with their conquerors. But there were those who did not submit, who fought and receded till they reached parts of the country where the conquerors did not care to seek for them; and there is no reason to doubt that the dark wild tribes of the interior hills and jungles of India, who differ so widely from the inhabitants of the plains, are the remnants of the stubborn Dasyas that did not yield. The condition of the conquering race is now well known, for it has been largely written upon; but of the aboriginal tribes who retreated before them the general knowledge is yet very inconsiderable. Every inaccessible jungle, hill-tract, and fen-land of the country is occupied by them; and they are to be seen there even now almost as isolated by manners, language, and prejudices of race from the population by whom they are surrounded as they were in the past.
Keywords: Sociology